2013
DOI: 10.1128/mcb.01257-12
|View full text |Cite
|
Sign up to set email alerts
|

Active Stabilization of Human Endothelial Nitric Oxide Synthase mRNA by hnRNP E1 Protects against Antisense RNA and MicroRNAs

Abstract: Human endothelial nitric oxide synthase (eNOS) mRNA is highly stable in endothelial cells (ECs). Posttranscriptional regulation of eNOS mRNA stability is an important component of eNOS regulation, especially under hypoxic conditions. Here, we show that the human eNOS 3= untranslated region (3= UTR) contains multiple, evolutionarily conserved pyrimidine (C and CU)-rich sequence elements that are both necessary and sufficient for mRNA stabilization. Importantly, RNA immunoprecipitations and RNA electrophoretic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 71 publications
3
75
0
Order By: Relevance
“…A number of ex vivo models support distinct biochemical functions for Pcbp1 and Pcbp2. For example, Pcbp1 is uniquely capable of regulating epithelial-mesenchymal transitions and stabilizing vascular nitric oxide synthase transcripts (37,42,70), while Pcbp2 specifically controls tumor suppressor genes in chronic myelogenous leukemia, poliovirus translation, and HIV gene expression (39)(40)(41). Thus, our in vivo analysis of embryogenesis is concordant with previous ex vivo studies in demonstrating that Pcbp1 and Pcbp2 play distinct roles in organism function.…”
Section: Discussionsupporting
confidence: 80%
“…A number of ex vivo models support distinct biochemical functions for Pcbp1 and Pcbp2. For example, Pcbp1 is uniquely capable of regulating epithelial-mesenchymal transitions and stabilizing vascular nitric oxide synthase transcripts (37,42,70), while Pcbp2 specifically controls tumor suppressor genes in chronic myelogenous leukemia, poliovirus translation, and HIV gene expression (39)(40)(41). Thus, our in vivo analysis of embryogenesis is concordant with previous ex vivo studies in demonstrating that Pcbp1 and Pcbp2 play distinct roles in organism function.…”
Section: Discussionsupporting
confidence: 80%
“…These regulatory factors often converge on the 3’ untranslated regions (3’UTRs) of mRNAs (Jens and Rajewsky, 2015). Juxtaposition of their binding sites contributes to combinatorial mechanisms of post-transcriptional gene regulation (Glorian et al, 2011, Zhang et al, 2008, Kundu et al, 2012, Young et al, 2012, Kim et al, 2009, Jafarifar et al, 2011, Ho et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Second, miR-765 can also directly inhibit eNOS expression by targeting at the 3′UTR of eNOS gene (Ho et al, 2013). Ho et al found that miR-765's knockdown effect on eNOS was only evident when the RNA stabilizing protein hnRNP-E1 was depleted (Ho et al, 2013). Normally, hnRNP-E1 is abundant in HUVECs, which might explain why we did not find any change in total-eNOS amount in HUVECs transfected with miR-765 (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Plenty studies supported that APLN enhances eNOS phosphorylation through ERK1/2, Akt, and AMPK cascades (Masri et al, 2004;Shan et al, 2011). Second, miR-765 can also directly inhibit eNOS expression by targeting at the 3′UTR of eNOS gene (Ho et al, 2013). Ho et al found that miR-765's knockdown effect on eNOS was only evident when the RNA stabilizing protein hnRNP-E1 was depleted (Ho et al, 2013).…”
Section: Discussionmentioning
confidence: 97%